2013
DOI: 10.3109/13816810.2013.833635
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CYP1B1 Mutation with Congenital Glaucoma and Total Aniridia

Abstract: CYP1B1 mutation related congenital glaucoma can present with an extreme form of anterior segment dysgenesis that includes recalcitrant glaucoma, corneal opacification and aniridia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…The conclusion is that the iris malformations in these patients may be due to mutation in another gene that has a role in the formation of the eye, and thus aniridia is phenotypically present (9). This has been supported by results of the study which showed that mutations in the CYP1B1 gene can lead to the appearance of congenital aniridia and glaucoma (10).…”
Section: Discussionsupporting
confidence: 75%
“…The conclusion is that the iris malformations in these patients may be due to mutation in another gene that has a role in the formation of the eye, and thus aniridia is phenotypically present (9). This has been supported by results of the study which showed that mutations in the CYP1B1 gene can lead to the appearance of congenital aniridia and glaucoma (10).…”
Section: Discussionsupporting
confidence: 75%
“…Genes such as GPATCH3 [ 26 ] and GUCA1C [ 27 ] have been identified as candidate CG genes, although their role in the disease remains to be confirmed. Remarkable phenotypic variability is also present in CYP1B1 -associated glaucoma, ranging from mild adult-onset goniodysgenesis to agenesis of the Schlemm canal [ 18 , 28 ] and complete aniridia [ 29 ]. This phenomenon suggests the existence of modifier factors in the phenotypic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Genes such as GPATCH3 [26] and GUCA1C [27] have been identified as candidate CG genes, although their role in the disease remains to be confirmed. Remarkable phenotypic variability is also present in CYP1B1-associated glaucoma, ranging from mild adult-onset goniodysgenesis to agenesis of the Schlemm canal [18,28] and complete aniridia [29]. This phenomenon suggests the existence of modifier factors in the phenotypic outcome.…”
Section: Introductionmentioning
confidence: 99%